The sustainable network : the accidental answer for a troubled planet - Sorensen, Sarah (Sebastopol, Calif. : O$1 (BReilly, s, 2009)
This book demonstrates how we can tackle challenges, ranging from energy conservation to economic and social innovation, using the global network of which the public Internet is just one piece. To help solve a myriad of problems today, author Sarah Sorensen points out that the best tool for enacting change already exists, lying literally at our fingertips. This book demystifies the power of the network and issues a strong call to action.
DedicationPrefaceChapter 1: I Am a NodeChapter 2: What Is the Network: How Does It Work?Chapter 3: Green by AccidentChapter 4: What Makes the Network Sustainable?Chapter 5: Broadband: What Is It?Chapter 6: Can the Internet Hit a Wall?Chapter 7: The Mobile MeChapter 8: Take It with YouChapter 9: The Network's Green FactorChapter 10: Carbon FootprintsChapter 11: Net Efficiencies: Maximizing Resources While Minimizing WasteChapter 12: What's So Smart About an Energy Grid?Chapter 13: DematerializationChapter 14: DetravelizationChapter 15: What Is the Network: How Is Telecommuting Enabled?Chapter 16: Pushing the BoundariesChapter 17: Data CenterChapter 18: Energy Efficiency MeasurementChapter 19: Doing Good by Doing RightChapter 20: Is Broadband Really That Important?Chapter 21: Sustainable ProvidersChapter 22: Net NeutralityChapter 23: Tearing Down Economic BoundariesChapter 24: Information Is KingChapter 25: EvolutionChapter 26: Network TimeChapter 27: Political SustainabilityChapter 28: Rocking the VoteChapter 29: The Right to Network UsageChapter 30: Challenges of the Networked WorldChapter 31: Network Defenses Depend on How Traffic Is SentChapter 32: I Am on the Net, Therefore I Am VulnerableChapter 33: Antisocial Network EngineeringChapter 34: Protect the NetChapter 35: The Last Best Place to Attack: Your MobileChapter 36: Government's Role in Protecting the Network's IntegrityChapter 37: 21st-Century Warfare: CyberattacksChapter 38: Social SustainabilityChapter 39: The Health NetChapter 40: Not by Accident: Social NetworkingChapter 41: Our Relationship with the NetworkA Quick Cheat Sheet of Common TermsNotesColophon
Includes bibliographical references (p. [313]-336) and index.
1
Keywords: Computer networks -- Environonmental aspects; Digital communications -- Environmental aspects; Sustainable development